Changes in Endocannabinoid Receptors and Enzymes in the Spinal Cord of SOD1(G93A) Transgenic Mice and Evaluation of a Sativex(®)‐like Combination of Phytocannabinoids: Interest for Future Therapies in Amyotrophic Lateral Sclerosis - Moreno‐Martet, Miguel (CNS Neurosci Ther, 2014)
AIMS: Cannabinoids afford neuroprotection in SOD1(G93A) mutant mice, an experimental model of amyotrophic lateral sclerosis (ALS). However, these mice have been poorly studied to identify alterations in those elements of the endocannabinoid system targeted by these treatments. Moreover, we studied the neuroprotective effect of the phytocannabinoid‐based medicine Sativex(®) in these mice. METHODS: First, we analyzed the endocannabinoid receptors and enzymes in the spinal cord of SOD1(G93A) transgenic mice at a late stage of the disease. Second, 10‐week‐old transgenic mice were daily treated with an equimolecular combination of Δ(9)‐tetrahydrocannabinol‐ and cannabidiol‐enriched botanical extracts (20 mg/kg for each phytocannabinoid). RESULTS: We found a significant increase of CB (2) receptors and NAPE‐PLD enzyme in SOD1(G93A) transgenic males and only CB (2) receptors in females. Pharmacological experiments demonstrated that the treatment of these mice with the Sativex(®)‐like combination of phytocannabinoids only produced weak improvements in the progression of neurological deficits and in the animal survival, particularly in females. CONCLUSIONS: Our results demonstrated changes in endocannabinoid signaling, in particular a marked up‐regulation of CB (2) receptors, in SOD1(G93A) transgenic mice, and provide support that Sativex(®) may serve as a novel disease‐modifying therapy in ALS.